The Identifikasi Aktor Kunci dan Potensi Modal Sosial dalam Mendukung Pelaksanaan Program KKN - Supriatiningsih, Supriatiningsih (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2026)
Community Service Program (Kuliah Kerja Nyata/KKN) is a form of community engagement aimed at encouraging community participation in local development processes. This activity was carried out in Pasar Manggis Subdistrict, Setiabudi District, South Jakarta, to identify environmental issues and promote community involvement in addressing these challenges. The implementation method used a participatory approach by actively involving community members in the stages of problem identification, activity planning, and program evaluation. Data collection techniques included field observations, community discussions, and activity documentation. The results indicate that one of the main issues faced by the community is environmental security, which still requires improvements in facilities and coordination among residents. However, the community still possesses relatively strong social capital, as reflected in the presence of cooperation activities, trust among residents, and participation in neighborhood initiatives. Therefore, strengthening community participation and collaboration among residents is essential to support safer and more sustainable community development